Portable American sign language system using RF signals and IoT technology for deaf-blind people - Khang, Adam Wong Yoon; Jamil Alsayaydeh, Jamil Abedalrahim; Mohamat Gani, Johar Akbar; Bascar, Tarani; Awang Teh, Azman; Pusppanathan, Jaysuman; Oliinyk, Andrii (Semarak Ilmu Publishing, 2025)
The Internet of Things (IoT) has revolutionized connectivity, enhancing accessibility to devices and information. This advancement addresses challenges faced by deaf-blind individuals, such as slow learning and memory issues. A new ASL learning kit has been developed to address these challenges, featuring physical and interactive elements for an engaging experience. Two learning methods are available: one involves RFID sign language cards tapped on an RFID reader, triggering an LCD visualizer with ASL alphabets and videos; the other method uses a Braille-embedded keyboard to provide audio feedback through ESpeak for ASL gestures. This ASL learning kit aims to boost the interest and effectiveness of deaf-blind students in learning ASL and Braille.